PENGARUH MEDIA SPIN THE WHEEL TERHADAP HASIL BELAJAR IPAS PADA SISWA KELAS VI SD - Arka Yuningrat, Ahmad; Rahmawati,S.Pd., M.Pd2, Ery; Wahju Andjariani,S.Sos., M.Pd, Endang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education is vital for the development of Indonesia, as it is everywhere else. Over the past decade, incorporating digital tools into the classroom has significantly bolstered educational advancements. This research holds weight due to its investigation of the educational possibilities of modern technologies, including Spin the Wheel media. . At SDN Kebonagung 2 in the IPAS subject (a fusion of science and social studies) The study made use of the latest Indonesian Independent Learning Curriculum during the second semester of the 2024/2025 school year. Two groups were created from the sample: a control group not using Spin the Wheel media and an experimental group. Instruments The results of the research highlighted a considerable difference between the initial evaluation and the follow- up evaluation for all participant categories, particularly the experimental group. achieving a higher average gain of 78.17 compared to the control group’s 69.33. Out of 20 questions, 12 were declared valid based on the validity test, The consistency assessment displayed a Cronbach's alpha value of 0.800, which exceeds the 0.6 benchmark, indicating high reliability. The t-test results confirmed that the use of Spin the Wheel significantly improved learning outcomes. Furthermore, The learners in the tested group exhibited a remarkably elevated degree of involvement, with an observation score of 91.5%. Consequently, in addition to improving learning results, this medium raised primary level pupil involvement in the IPAS curriculum.